HELICOBACTER PYLORI AND THE ATHEROGENIC PROCESS IN CARDIOVASCULAR DISEASE - Carvalho, Nuno (2018)
Background: Conventional risk factors do not explain completely the atherogenic process. Chronic Helicobacter pylori (HP) infection may cause arterial inflammation and has been epidemiologically linked to the occurrence of atherosclerosis. Studies about the association of HP infection with peripheral arterial disease are limited. Objective: Evaluate the presence of HP using a monoclonal antibody anti-HP in the atherosclerotic plaques of the superficial femoral artery in patients submitted to amputation above-knee. Material and methods: We searched for the presence of HP in 29 non-consecutive patients with Leriche-Fontaine grade IV lower limb ischemia, submitted to amputation above-knee. Femoral artery was isolated and an atherosclerotic plaque specimen immediately distal to the amputation level, was removed, fixed in formalin and evaluated for HP, using a mono clonal antibody, anti-HP. Results: The mean age of the 29 patients was 82 years. 18 were men (62.1 %). Risk factors for cardiovascular disease were present in the majority of patients. Only one patient had known history of HP infection in the past. Morbidity rate was 30%. The mortality rate was 13.8 % (4 cases). In all cases, anti-HP showed no evidence of HP at the atherosclerotic plaque. Discussion/Conclusion: HP infection has been associated both epidemiologically and pathogenetically with atherosclerosis. However, HP was not found in this study at the atherosclerotic plaques of the superficial femoral artery.